Multiple regimes of operation in bimodal AFM: understanding the energy of cantilever eigenmodes - Kiracofe, Daniel; Raman, Arvind; Yablon, Dalia (Beilstein Journal of Nanotechnology, 2013)
One of the key goals in atomic force microscopy (AFM) imaging is to enhance material property contrast with high resolution. Bimodal AFM, where two eigenmodes are simultaneously excited, confers significant advantages over conventional single-frequency tapping mode AFM due to its ability to provide contrast between regions with different material properties under gentle imaging conditions. Bimodal AFM traditionally uses the first two eigenmodes of the AFM cantilever. In this work, the authors explore the use of higher eigenmodes in bimodal AFM (e.g., exciting the first and fourth eigenmodes). It is found that such operation leads to interesting contrast reversals compared to traditional bimodal AFM. A series of experiments and numerical simulations shows that the primary cause of the contrast reversals is not the choice of eigenmode itself (e.g., second versus fourth), but rather the relative kinetic energy between the higher eigenmode and the first eigenmode. This leads to the identification of three distinct imaging regimes in bimodal AFM. This result, which is applicable even to traditional bimodal AFM, should allow researchers to choose cantilever and operating parameters in a more rational manner in order to optimize resolution and contrast during nanoscale imaging of materials.
Keywords: atomic force microscopy; bimodal AFM; cantilever eigenmodes; polymer characterization

Polymer Microscopy - Sawyer, L. C.; Grubb, D. T.; Meyers, G. F. (Springer Verlag, 2008)

(untitled) - Rodríguez, T. R.; García, R. (Appl. Phys. Lett., 2004)

(untitled) - Lozano, J. R.; García, R. (Phys. Rev. B, 2009)

(untitled) - Dietz, C.; Zerson, M.; Riesch, C.; Gigler, A. M.; Stark, R. W.; Rehse, N.; Magerle, R. (Appl. Phys. Lett., 2008)

(untitled) - Martínez, N. F.; Lozano, J. R.; Herruzo, E. T.; García, F.; Richter, C.; Sulzbach, T.; García, R. (Nanotechnology, 2008)

(untitled) - Li, J. W.; Cleveland, J. P.; Proksch, R. (Appl. Phys. Lett., 2009)

(untitled) - Baumann, M.; Stark, R. W. (Ultramicroscopy, 2010)

(untitled) - Gigler, A. M.; Dietz, C.; Baumann, M.; Martinez, N. F.; García, R.; Stark, R. W. (Beilstein J. Nanotechnol., 2012)

(untitled) - Solares, S. D.; Chawla, G. (J. Appl. Phys., 2010)

(untitled) - García, R.; Paulo, A. S. (Phys. Rev. B, 2000)

(untitled) - Hutter, J. L.; Bechhoefer, J. (Rev. Sci. Instrum., 1993)

(untitled) - Butt, H.-J.; Jaschke, M. (Nanotechnology, 1995)

(untitled) - Green, C. P.; Sader, J. E. (J. Appl. Phys., 2005)

(untitled) - Kiracofe, D.; Raman, A. (Nanotechnology, 2011)

(untitled) - Yablon, D. G.; Gannepalli, A.; Proksch, R.; Killgore, J.; Hurley, D. C.; Grabowski, J.; Tsou, A. H. (Macromolecules, 2012)

(untitled) - Lozano, J. R.; García, R. (Phys. Rev. Lett., 2008)

(untitled) - Proksch, R. (Appl. Phys. Lett., 2006)

(untitled) - Stark, R. W. (Appl. Phys. Lett., 2009)

(untitled) - Melcher, J.; Carrasco, C.; Xu, X.; Carrascosa, J. L.; Gómez-Herrero, J.; de Pablo, P. J.; Raman, A. (Proc. Natl. Acad. Sci. U. S. A., 2009)

VEDA: Virtual Environment for Dynamic AFM

(untitled) - Kiracofe, D.; Melcher, J.; Raman, A. (Rev. Sci. Instrum., 2012)

(untitled) - Melcher, J.; Hu, S.; Raman, A. (Rev. Sci. Instrum., 2008)

(untitled) - Kiracofe, D.; Raman, A. (J. Appl. Phys., 2010)

(untitled) - Melcher, J.; Hu, S.; Raman, A. (Appl. Phys. Lett., 2007)

(untitled) - García, R.; Gómez, C. J.; Martinez, N. F.; Patil, S.; Dietz, C.; Magerle, R. (Phys. Rev. Lett., 2006)